The TonB Dimeric Crystal Structures Do Not Exist In Vivo - Kathleen Postle (American Society for Microbiology, 2010)
ABSTRACT The TonB system energizes transport of nutrients across the outer membrane of Escherichia coli using cytoplasmic membrane proton motive force (PMF) for energy. Integral cytoplasmic membrane proteins ExbB and ExbD appear to harvest PMF and transduce it to TonB. The carboxy terminus of TonB then physically interacts with outer membrane transporters to allow translocation of ligands into the periplasmic space. The structure of the TonB carboxy terminus (residues ~150 to 239) has been solved several times with similar results. Our previous results hinted that in vitro structures might not mimic the dimeric conformations that characterize TonB in vivo. To test structural predictions and to identify irreplaceable residues, the entire carboxy terminus of TonB was scanned with Cys substitutions. TonB I232C and N233C, predicted to efficiently form disulfide-linked dimers in the crystal structures, did not do so. In contrast, Cys substitutions positioned at large distances from one another in the crystal structures efficiently formed dimers. Cys scanning identified seven functionally important residues. However, no single residue was irreplaceable. The phenotypes conferred by changes of the seven residues depended on both the specific assay used and the residue substituted. All seven residues were synergistic with one another. The buried nature of the residues in the structures was also inconsistent with these properties. Taken together, these results indicate that the solved dimeric crystal structures of TonB do not exist. The most likely explanation for the aberrant structures is that they were obtained in the absence of the TonB transmembrane domain, ExbB, ExbD, and/or the PMF. IMPORTANCE The TonB system of Gram-negative bacteria is an attractive target for development of novel antibiotics because of its importance in iron acquisition and virulence. Logically, therefore, the structure of TonB must be accurately understood. TonB functions as a dimer in vivo, and two different but similar crystal structures of the dimeric carboxy-terminal ~90 amino acids gave rise to mechanistic models. Here we demonstrate that the crystal structures, and therefore the models based on them, are not biologically relevant. The idiosyncratic phenotypes conferred by substitutions at the only seven functionally important residues in the carboxy terminus suggest that similar to interaction of cytochromes P450 with numerous substrates, these residues allow TonB to differentially interact with different outer membrane transporters. Taken together, data suggest that TonB is maintained poised between order and disorder by ExbB, ExbD, and the proton motive force (PMF) before energy transduction to the outer membrane transporters.